Numerical simulation of multilayer cellular scaffolds with 3D and 1D elements - Hamid Reza khanaki; Sadegh Rahmati; Mohammad Nikkhoo; Mohammad Haghpanahi; Javad Akbari (International Journal of Advanced Design and Manufacturing Technology, 2020)
In this paper, an attempt has been made to provide a numerical method for investigating the mechanical properties of multilayer scaffolding. These scaffolds can be used as implants in bone fractures. For this purpose two numerical simulation methods are introduced to predict the elastic properties of multilayer cell scaffolds. These simulations are based on two models: a 3D model with a volumetric element, and a 1D model with a linear element. To compare the results of these models, three types of two- and three-layer titanium alloy scaffolds have been simulated by the two methods. Also, Young's modulus of the scaffolds has been compared with the experimental conclusions of earlier studies. The results confirm that simulations with 1D models are more cost-effective compared to 3D ones. Additionally, because of the more reliable agreement of Young's modulus results of numerical modeling with the linear element (1.8 to 5 times) compared to the volumetric element (11 to 23 times) compared to the experimental findings, the numerical method with the linear elements can be a reliable tool for studying multilayer scaffoldings.